Impact of selection regime and introgression on deltamethrin resistance in the arbovirus vector Aedes aegypti – a comparative study between contrasted situations in New Caledonia and French Guiana. Issue 12 (26th August 2021) - Cattel, Julien; Minier, Marine; Habchi‐Hanriot, Nausicaa; Pol, Morgane; Faucon, Frederic; Gaude, Thierry; Gaborit, Pascal; Issaly, Jean; Ferrero, Emma; Chandre, Fabrice; Pocquet, Nicolas; David, Jean‐Philippe; et al.
Abstract: BACKGROUND: Pyrethroid insecticides such as deltamethrin have been massively used against Aedes aegypti leading to the spread of resistance alleles worldwide. In an insecticide resistance management context, we evaluated the temporal dynamics of deltamethrin resistance using two distinct populations carrying resistant alleles at different frequencies. Three different scenarios were followed: a continuous selection, a full release of selection, or a repeated introgression with susceptible individuals. The responses of each population to these selection regimes were measured across five generations by bioassays and by monitoring the frequency of knockdown resistance ( kdr ) mutations and the transcription levels and copy number variations of key detoxification enzymes. RESULTS: Knockdown resistance mutations, overexpression and copy number variations of detoxification enzymes as a mechanism of metabolic resistance to deltamethrin was found and maintained under selection across generations. On comparison, the release of insecticide pressure for five generations did not affect resistance levels and resistance marker frequencies. However, introgressing susceptible alleles drastically reduced deltamethrin resistance in only three generations. CONCLUSION: The present study confirmed that strategies consisting to stop deltamethrin spraying are likely to fail when the frequencies of resistant alleles are too high and the fitness cost associated to resistance is low. In dead‐end situations like in French Guiana where alternative insecticides are not available, alternative control strategies may provide a high benefit for vector control, particularly if they favor the introgression of susceptible alleles in natural populations. © 2021 Society of Chemical Industry. Abstract : We evaluated the temporal dynamics of deltamethrin resistance following three different scenarios: a continuous selection, a full release of the selection, or a repeated introgression with susceptible individuals.